ANALISIS PRESTASI KERJA MOTOR 4 TAK DENGAN PENGGUNAAN TURBO CYCLONE - Nely Ana Mufarida (Universitas Muhammadiyah Jember, 2016)
AbstractTechnological developments in the automotive field, especially in the motor fuel continued to experience improvements in order to provide comfort without neglecting the safety factor and the ability to produce large power. One attempt to do to generate greater power is to increase the efficiency of the motor fuel to improve combustion processes that occur in the combustion chamber. This is also done by Sei Y Kim through his invention called the Turbo Cyclone. There are four experiments conducted namely intake manifold that does not use turbo cyclone (standard), and use the turbo cyclone with angle variety of 55°, 65°, and 75°. The motors are in use is the motor 4 stroke 100cc. Fuel used is LPG. Based on the results of the study showed that in use with turbo cyclone with an angle of 65°on intake manifolds improve engine performance that is equal to 4.89 Nm to 0.15 Nm increase or an increase of 3.16% compared with the standard views of torque while the maximum power generated on the variation of fin 65°amounted to 4.529 Hp rose 5.829% or 0.252 hp compared with the standard.Keywords:4 stroke 100cc engine, turbo cyclone, intake manifold